2021
DOI: 10.1016/j.ijid.2020.11.162
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Epidemiology of Invasive Meningococcal Disease and Vaccination Strategies in North Africa

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Improved surveillance systems could help improve disease monitoring. The Global Burden of Disease Study showed that six of the ten countries with the highest number of meningitis deaths (all-causes) are in the African meningitis belt region; though data for older adults from these countries are lacking, suggesting a potential underreporting of cases in older adults in this region [ 41 , 91 , 92 ]. Since we restricted our search to English langauge papers only we decided to exclude date from outside North American and Europe but it is interesting to note that we identified only eleven English language published studies of IMD in older adults from countries outside Europe or North America, which appers to be consistent with previous research highlighting the lack of regional data, particularly from South-East Asia and the Eastern Mediterranean [ 3 ] in non-native languages.…”
Section: Discussionmentioning
confidence: 99%
“…Improved surveillance systems could help improve disease monitoring. The Global Burden of Disease Study showed that six of the ten countries with the highest number of meningitis deaths (all-causes) are in the African meningitis belt region; though data for older adults from these countries are lacking, suggesting a potential underreporting of cases in older adults in this region [ 41 , 91 , 92 ]. Since we restricted our search to English langauge papers only we decided to exclude date from outside North American and Europe but it is interesting to note that we identified only eleven English language published studies of IMD in older adults from countries outside Europe or North America, which appers to be consistent with previous research highlighting the lack of regional data, particularly from South-East Asia and the Eastern Mediterranean [ 3 ] in non-native languages.…”
Section: Discussionmentioning
confidence: 99%
“…One important point is that some level of underreporting for IMD in KSA may exist, a feature also apparent in other surveillance studies in the MENA regions [ 25 , 48 , 49 ]. We suggest this for two reasons.…”
Section: Discussionmentioning
confidence: 71%
“…Most global reviews, including regional reviews from the Global Meningococcal Initiative, highlight limited recent epidemiological data available from many countries in Asia, and from the Middle East and North African (MENA) regions. [ 1 , 2 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, the distribution of IMD by serogroup is W (42%), B (21%), "not defined" (15%), and Y (13%) (44). In Morocco, IMD is considered endemic with estimated incidence and death rates for meningococcal meningitis as 13.24/100,000 and 0.22/100,000, respectively (18). While, Tunisia has relatively lower incidence and death rates estimated to be 6.80/100,000 and 0.08/100,000, respectively (18).…”
Section: Meningococcal Infectionmentioning
confidence: 99%
“…In Morocco, IMD is considered endemic with estimated incidence and death rates for meningococcal meningitis as 13.24/100,000 and 0.22/100,000, respectively (18). While, Tunisia has relatively lower incidence and death rates estimated to be 6.80/100,000 and 0.08/100,000, respectively (18). Meningococcal serogroup B (MenB) is highly prevalent in most of North Africa (45).…”
Section: Meningococcal Infectionmentioning
confidence: 99%